Victorian Designs of Industrial Desire - Béatrice Laurent (Cahiers Victoriens et Edouardiens)
The Victorian fascination with the world of manufacture—exemplified in the Great Exhibition of 1851—was concomitant with, and probably fuelled by, progress in technical drawing fluency and literacy. Periodicals such as The Mechanics’ Magazine (founded 1823) and The English Mechanic and World of Science (founded 1865) included increasingly sophisticated illustrations which taught their readers to look at objects and machines differently. The necessity to look beyond the surface and into the hidden mechanical devices demanded a level of abstraction that some philanthropists deemed essential to improve the condition of the artisans. Their self-appointed ‘mission’ to make ‘an ‘unlearned people’ learned in ‘common things’ contended that technical drawing ‘materially assists the understanding of machinery, not only by illustrations, but by teaching the mind to separate the parts of a whole and to note their relation’1. This form of industrial education resulted in a training of the eye and the mind to operate according to non-mimetic, purely conceptual codes. The cultural impact of this revolution in the act of seeing reached far beyond the field of technical drawing, as this paper proposes to demonstrate.